Culture of Nile tilapia in a biofloc system with different sources of carbon (Revista Ciência Agronômica, 2018)
The aim of this work was to evaluate the effects of using different sources of organic carbon on water quality,growth performance and the acceptability of Nile tilapia (Oreochromis niloticus) fillets grown in a biofloc system. Theexperiment was carried out over 145 days at the Aquaculture Station of the Federal Rural University of Pernambuco, Brazil.Fish of 72.6 ± 6.83 g were stored (35 fish m-3) in 19 circular tanks (800 L) in a completely randomised experimental design withthree treatments, including as a source of carbon, sugar (SUG), liquid molasses (MOL) and molasses powder (MOP), each withfive replications, and one control treatment (CTL) without bioflocs, with four replications. Dissolved oxygen concentrationswere significantly higher (P≤0.05) in the tanks with no bioflocs due to the absence of bacterial biomass. Total ammoniacalnitrogen (TAN) showed a statistical difference (P≤0.05) between the SUG treatment and the other treatments with bioflocs,having the lowest concentration of 2.53 mg L-1. Survival was greater than 80%, with no statistical difference between treatments(P>0.05); productivity varied from 9.72 (SUG) to 14.22 kg m-3 (CTL) (P≤0.05). Water consumption in the tanks with bioflocswas 11.8 times lower than in the control (CTL). The tilapia fillets from the bioflocs with sugar were preferred by the evaluators,with a score of 7.77 (like moderately to like very much). The carbon sources used (molasses and sugar) can be employed in theculture of O. niloticus tilapia in bioflocs with no damage to the culture water or to productivity.